The Relevance of Al-Ghazali and Ibn-Khaldun's Education Concepts in Era 4.0. - Hardika Saputra; Dwi Kurniawan; Retno Fentari (Al Qalam: Jurnal Ilmiah Keagamaan dan Kemasyarakatan, 2022)
The purpose of this study is to explore the meaning of the thoughts of Al-Ghazali and Ibn Khaldun and the relevance of these two thoughts during the industrial revolution 4.0. This research uses library research method with data collection techniques sourced from written texts which are then analyzed using content analysis techniques. The concept of education in Islam is not only a question of how to instill values to defend oneself from the influence of life in the Industrial Revolution era. However, the most important thing is how the moral values that will be instilled can solve problems in human life, such as ignorance, poverty, and backwardness in various fields. This proves that Islamic education has an important role in the process of forming human beings who are cognitively intelligent but also have a good personality and the application of Islamic teachings in life. This research contributes to the study of Islamic thinkers and the contribution of their thoughts in the era of the industrial revolution 4.0